Critical role for tumor necrosis factor alpha in controlling the number of lumenal pathogenic bacteria and immunopathology in infectious colitis - Gonçalves, N; Ghaem-Maghami, M; Monteleone, G; Frankel, G; Dougan, G; Lewis, D; Simmons, C; Macdonald, T (American Society for Microbiology, 2001)
Infection of mice with the intestinal bacterial pathogenCitrobacter rodentium results in colonic mucosal hyperplasia and a local Th1 inflammatory response similar to that seen in mouse models of inflammatory bowel disease. In these latter models, and in patients with Crohn's disease, neutralization of tumor necrosis factor alpha (TNF-α) is of therapeutic benefit. Since there is no information on the role of TNF-α in either immunity to noninvasive bacterial pathogens or on the role of TNF-α in the immunopathology of infectious colitis, we investigated C. rodentiuminfection in TNFRp55−/− mice. In TNFRp55−/−mice, there were higher colonic bacterial burdens, but the organisms were cleared at the same rate as C57BL/6 mice, showing that TNF-α is not needed for protective antibacterial immunity. The most striking feature of infection in TNFRp55−/−mice, however, was the markedly enhanced pathology, with increased mucosal weight and thickness, increased T-cell infiltrate, and a markedly greater mucosal Th1 response. Interleukin-12 p40 transcripts were markedly elevated in C. rodentium-infected TNFRp55−/− mice, and this was associated with enhanced mucosal STAT4 phosphorylation. TNF-α is not obligatory for protective immunity to C. rodentium in mice; however, it appears to play some role in downregulating mucosal pathology and Th1 immune responses.